Poly(ADP‐ribosyl)ation of BRD7 by PARP1 confers resistance to DNA‐damaging chemotherapeutic agents. (2nd April 2019) - Hu, Kaishun; Wu, Wenjing; Li, Yu; Lin, Lehang; Chen, Dong; Yan, Haiyan; Xiao, Xing; Chen, Hengxing; Chen, Zhen; Zhang, Yin; Xu, Shuangbing; Guo, Yabin; et al.
Abstract: The bromodomain‐containing protein 7 (BRD7) is a tumour suppressor protein with critical roles in cell cycle transition and transcriptional regulation. Whether BRD7 is regulated by post‐translational modifications remains poorly understood. Here, we find that chemotherapy‐induced DNA damage leads to the rapid degradation of BRD7 in various cancer cell lines. PARP‐1 binds and poly(ADP)ribosylates BRD7, which enhances its ubiquitination and degradation through the PAR‐binding E3 ubiquitin ligase RNF146. Moreover, the PARP1 inhibitor Olaparib significantly enhances the sensitivity of BRD7‐positive cancer cells to chemotherapeutic drugs, while it has little effect on cells with low BRD7 expression. Taken together, our findings show that PARP1 induces the degradation of BRD7 resulting in cancer cell resistance to DNA‐damaging agents. BRD7 might thus serve as potential biomarker in clinical trial for the prediction of synergistic effects between chemotherapeutic drugs and PARP inhibitors. Synopsis: PARP1 promotes the PARylation and degradation of the tumor suppressor BRD7 thereby enhancing survival of cancer cells in response to DNA‐damaging agents. BRD7 interacts with PARP1 via three potential PAR‐binding motifs. Inhibiting PARylation of PARP1 by Olaparib disrupted the interaction of BRD7 with PARP1. BRD7 protein is subjected to PARP1‐mediated poly(ADP‐ribosyl)ation and subsequent ubiquitylation by RNF146, leading to resistance to DNA‐damaging agents of cancer cells. Abstract : PARP1 promotes the PARylation and degradation of the tumor suppressor BRD7 thereby enhancing survival of cancer cells in response to DNA‐damaging agents.